The Influence of Authoritarian Parenting on the Development of Early Childhood Creativity - Fitriana, Laila; Purwastuti, Lusila Andriani (FKIP Universitas Lampung, 2020)
The Influence of Authoritarian Parenting on the Development of Early Childhood Creativity. Objectives: This study aims to reveal whether there is an influence of authoritarian parenting on the development of early childhood creativity. Methods: Ex Post Facto quantitative research involved 100 children aged 4-5 years and their parents, and 18 teachers from 9 kindergartens in Jambi City. Data were analyzed using simple linear regression analysis to reveal the effect of authoritarian parenting on the development of creativity. Findings: Simple linear regression test for authoritarian parenting has a significance value of 0.003 (P <0.05) which means that it influences children’s creativity, children become unconfident, afraid to do something, and children tend to be quieted. Parents who apply the majority authoritarian parenting background in high school education. Conclusion: There is a negative influence of authoritarian parenting on the development of early childhood creativity.Keywords: authoritarian parenting, development of creativity, early childhood.DOI: 10.23960/jpp.v10.i2.202011